(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Future shopping applications collect basic profile information of the person and provide great service on recommending books, electronics and other products based on user profile, previous shopping history and relationships between the items categories derived from purchases of all the users on the site. E.g. if someone is looking at action movies it can recommend similar category or a category that the shopper is likely to be associated with. The mining of user’s profile greatly enhances a person’s shopping experience on modern online shops. The main purpose of this paper is solving the privacy and security issues.